2019
DOI: 10.1186/s12968-019-0548-1
|View full text |Cite
|
Sign up to set email alerts
|

Size of carotid artery intraplaque hemorrhage and acute ischemic stroke: a cardiovascular magnetic resonance Chinese atherosclerosis risk evaluation study

Abstract: Background To determine the usefulness of the size of carotid artery intraplaque hemorrhage (IPH) in discriminating the risk of acute ischemic stroke using cardiovascular magnetic resonance (CMR) vessel wall imaging. Methods Symptomatic patients with carotid atherosclerotic plaque who participated in a cross-sectional, multicenter study of CARE-II (NCT02017756) were included. All patients underwent carotid and brain CMR imaging. Carotid plaque burden and the size of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…These findings confirm that IPH volume is higher in plaques causing cerebrovascular events. 2,3,5,6,31,32 Of interest, there was no difference in lipid-IPH volume tissue, whereas the total lipid volume showed a statistically significant difference. This finding can be explained because in the old classification the lipid volume class included all the voxels <60 HU (and therefore also the IPH component); these results suggest that tissues with an attenuation between 26 to 59 HU, namely fatty components, are not associated with the presence of cerebrovascular events.…”
Section: Discussionmentioning
confidence: 83%
“…These findings confirm that IPH volume is higher in plaques causing cerebrovascular events. 2,3,5,6,31,32 Of interest, there was no difference in lipid-IPH volume tissue, whereas the total lipid volume showed a statistically significant difference. This finding can be explained because in the old classification the lipid volume class included all the voxels <60 HU (and therefore also the IPH component); these results suggest that tissues with an attenuation between 26 to 59 HU, namely fatty components, are not associated with the presence of cerebrovascular events.…”
Section: Discussionmentioning
confidence: 83%
“…Carotid plaque burden was significantly associated with ipsilateral acute cerebral infarction volume independent of the degree of carotid stenosis (115). Recently Liu et al showed that carotid plaque burden in patients with ≥1.5 mm carotid plaques was associated with the presence of acute stroke (116). Based on numerous ultrasound studies, it is well known that plaque burden is a better parameter for risk prediction than measurement of the common carotid artery intima-media thickness (73).…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
“…In the present study, the presence of LRNC and maximum area percentage of IPH were negatively correlated with the DR CBF but the correlation was weak. A study by Liu et al demonstrated that the size of IPH increased the risk of acute cerebral infarct 29 . Impaired microcirculation in carotid stenotic patients with LRNC might partially account for the smaller improvement of CBF after removing the plaques.…”
Section: Discussionmentioning
confidence: 99%